IMPLEMENTASI PERATURAN PEMERINTAH RI NOMOR 53 TAHUN 2010 TENTANG DISIPLIN PEGAWAI NEGERI SIPIL PADA SEKRETARIAT DAERAH KABUPATEN MESUJI - Rola Pola Anto; Adrian Tawai; Muzairi Muzairi (e-JKPP, 2021)
The problems in this research are: (1) How to implement the policy of the Republic of Indonesia Government Regulation Number 53 of 2010 concerning Civil Servant Discipline at the Regional Secretariat of Mesuji Regency. (2) What aspects hinder the implementation of the policies of the Government of the Republic of Indonesia Number 53 of 2010 concerning Discipline of Civil Servants at the Regional Secretariat of Mesuji Regency. This research design is to use a qualitative research type with descriptive analysis method. The use of this method is to describe the implementation of the policy of the Government of the Republic of Indonesia Number 53 of 2010 concerning Discipline of Civil Servants at the Regional Secretariat of Mesuji Regency, qualitatively examining how all data is obtained directly from informants in the field using interviews and observations. The results showed that the Implementation of Government Regulation No. 53 of 2010, has been implemented, but not optimal, employees who have good discipline are proven to show better performance compared to those who do not have good discipline. It can be seen that there are still state civil servants who often enter the office late and some often leave before office hours, without any clear reason, and this is also strengthened by employee performance reports. Obstructing aspects, namely in the application of employee discipline is a lack of knowledge about work procedures and standard operating procedures, which results in reduced work results, relatively low number of employees, and relatively limited office work facilities, and frequent power outages, so that time reduced work and relatively low quality of work. Thus, that the application of employee discipline in carrying out their duties is often neglected, many stakeholders have not expected sanctions for employees who violate the policies of the Republic of Indonesia Government Regulation No. 53 of 2010 concerning the Discipline of the State Civil Apparatus at the Regional Secretariat of Mesuji Regency.